Experimental and computational characterisation of an artificial light harvesting complex. Issue 6 (24th January 2023) - Slimani, Sabrina L.; Kostecki, Roman; Kursunlu, Ahmed Nuri; Kee, Tak W.; Tapping, Patrick C.; Mak, Adrian M.; Quach, James Q.
Abstract : The search for quantum behaviour within a BODIPY light-harvesting complex reveals coherent oscillations at 100 cm −1 and 600 cm −1 . Abstract : Photosynthesis has been shown to be a highly efficient process for energy transfer in plants and bacteria. Like natural photosynthetic systems, the artificial light harvesting complex (LHC) BODIPY pillar[5]arene exhibits Förster resonance energy transfer (FRET). However, extensive characterisation of the BODIPY pillar[5]arene LHC to determine its suitability as an artificial LHC has yet to occur. In this paper we experimentally and computationally investigate the photophysical properties of the LHC by comparing the light absorption of the BODIPY LHC to individual BODIPY chromophores. Our results show evidence for quantum coherence, with oscillation frequencies of 100 cm −1 and 600 cm −1, which are attributable to vibronic, or exciton–phonon type coupling. Computational analysis suggests strong couplings of the molecular orbitals of the LHC resulting from the stacking of neighbouring BODIPY chromophore units. Interestingly, we find a 40% reduction in the absorbance of light for the BODIPY LHC compared to the individual chromophores which we attribute to electronic interactions between the conjugated π-systems of the BODIPY chromophores and the pillar[5]arene backbone.